Computed tomography analysis of coronary ostia location following valve‐in‐valve transcatheter aortic valve replacement with the ACURATE neo valve: Implications for coronary access. Issue 3 (14th February 2021) - Khokhar, Arif A.; Laricchia, Alessandra; Ponticelli, Francesco; Kim, Won‐Keun; Gallo, Francesco; Regazzoli, Damiano; Toselli, Marco; Sticchi, Alessandro; Ruggiero, Rossella; Cereda, Alberto; Zlahoda‐Huzior, Adriana; Fisicaro, Andrea; et al.
Abstract: Background: Valve‐in‐valve transcatheter aortic valve replacement (ViV‐TAVR) is an emerging alternative to re‐do surgery. However, the challenge of coronary access (CA) following ViV‐TAVR is a potential limitation as TAVR expands to younger lower‐risk populations. Objectives: Using post‐implantation computed tomography (CT) scans to evaluate the geometrical relationship between coronary ostia and valve frame in patients undergoing ViV‐TAVR with the ACURATE neo valve. Methods: Post‐implant CT scans of 18 out of 20 consecutive patients treated with the ACURATE neo valve were analyzed. Coronary ostia location in relation to the highest plane (HP) (highest point of the ACURATE neo or surgical valve) was determined. Ostia located below the highest plan were further subclassified according to the gap available between the transcatheter heart valve frame and ostium (transcatheter‐to‐coronary [TTC] distance). The impact implantation depth has on these geometrical relationships was evaluated. Results: A total of 21 out of 36 coronary ostia (58%) were located below the level of the HP with the left coronary artery (36%) more likely to be affected than the right (22%). Further sub‐classification of these ostia revealed a large (>6 mm), moderate (4–6 mm), and small (<4 mm) TTC distance in 57% (12/21), 38% (8/21), and in 6% (1/18) of cases, respectively. At an implantation depth <4 mm compared to >4 mm, all ostia were located below the HP with no difference in post‐procedural mean gradients (14.5 mmHg ± 4.7 vs. 12.6 mmHg ± 5.8; p = .5, 95%CI 3.8–7.5). Conclusions: CA following ACURATE neo implantation for ViV‐TAVR could potentially be challenging in a significant proportion of patients and specific consideration should be given to the implantation depth.